Modeling through the centuries and the beginning of fashion (ModaPalavra e-periódico, 2013)
The present article seeks to realize a historical contextualization of bibliographic nature that persuits to introduce the transformations in clothes shaping, in haute couture and prêt-aporter, in the course of fashion history.
Keywords: fashion; shaping; historic context